Correlation analysis of vaginal flora and immune function Th1/Th2 imbalance in women with high-risk HPV infections in the female reproductive tract: HPV infection and vaginal flora correlation in women - Zheng, Jingjing; Zhao, Rongwei; Deng, Chunxia (Cellular and Molecular Biology, 2024)
The purpose of this study was to analyze the correlation between vaginal flora and immune function Type 1 helper T cells/Type 2 helper T cells imbalance in females having HPV infections at high risk within the female reproductive tract. We selected 150 female patients who visited our hospital for reproductive tract inflammation between March 2019 and March 2021. They were divided into high-risk HPV-positive and high-risk HPV-negative groups according to the results of the HPV tests. Vaginal flora composition, density, diversity, and Th1/Th2 immune cell cytokine expression were assessed, and their correlations were analyzed. Compared to the HPV-negative group at high risk, the HPV-positive group at high risk exhibited significantly higher rates of Lactobacillius abnormalities, Chlamydia trachomatis and Mycoplasma urealyticum positivity(P<0.05). However, no statistically significant differences in the rates of Neisseria gonorrhoeae, bacterial vaginosis, mould, and trichomonad positivity were observed in both groups (P>0.05). The high-risk HPV-positive group displayed significantly higher rates of abnormal vaginal flora density and diversity compared to the HPV-negative group at high risk (P < 0.05). Compared to the HPV-negative group at high risk, the HPV-positive group at high risk exhibited significantly lower expression levels of Th1, Th1/Th2, IFN-γ, and IL-2 and higher expression levels of Th2, IL-4, and IL-10(P<0.05). Among patients having HPV infections at high risk, those with abnormal vaginal flora had lower expression levels of Th1, Th1/Th2, IFN-γ, and IL-2 and higher expression levels of Th2, IL-4, and IL-10 compared to those with normal vaginal flora, all of which were statistically significant(P<0.05). Vaginal flora dysbiosis was correlated with Th1/Th2 imbalance (P<0.05). Women with high-risk HPV infections in the female reproductive tract exhibit abnormal vaginal flora and immune function Th1/Th2 imbalance, characterized by a shift from Th1 to Th2. Moreover, there is a close correlation between vaginal flora dysbiosis and immune function Th1/Th2 imbalance.